2021
DOI: 10.1159/000517169
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Suicidal Thoughts and Behaviors and Genetic Liability for Cognitive Performance, Depression, and Risk-Taking in a High-Risk Sample

Abstract: <b><i>Background:</i></b> Suicidal thoughts and behaviors (STBs) and nonsuicidal self-injury (NSSI) behaviors are moderately heritable and may reflect an underlying predisposition to depression, impulsivity, and cognitive vulnerabilities to varying degrees. <b><i>Objectives:</i></b> We aimed to estimate the degrees of association between genetic liability to depression, impulsivity, and cognitive performance and STBs and NSSI in a high-risk sample. <b><i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Even those adjusted FGRS estimates that differ significantly from the null hypothesis (i.e., OR = 1) are of small effect size, particularly relative to the effect sizes observed for several of the phenotypic registrations. Standard polygenic risk scores based on individual-level molecular data, when derived from and applied to psychiatric outcomes, vary in their estimated effects, but it is not unusual to see ORs that are higher than those in the current report (Campos et al, 2021;Fanelli et al, 2022;Johnson et al, 2021). However, the nature of our research question -i.e., whether the aggregate genetic risk can distinguish between members of two groups who might overlap considerably -is somewhat more nuanced than, for example, efforts to test whether polygenic scores are associated with more clearly delineated groups such as those with versus without schizophrenia.…”
Section: Discussionmentioning
confidence: 62%
“…Even those adjusted FGRS estimates that differ significantly from the null hypothesis (i.e., OR = 1) are of small effect size, particularly relative to the effect sizes observed for several of the phenotypic registrations. Standard polygenic risk scores based on individual-level molecular data, when derived from and applied to psychiatric outcomes, vary in their estimated effects, but it is not unusual to see ORs that are higher than those in the current report (Campos et al, 2021;Fanelli et al, 2022;Johnson et al, 2021). However, the nature of our research question -i.e., whether the aggregate genetic risk can distinguish between members of two groups who might overlap considerably -is somewhat more nuanced than, for example, efforts to test whether polygenic scores are associated with more clearly delineated groups such as those with versus without schizophrenia.…”
Section: Discussionmentioning
confidence: 62%
“…Recent multivariate genome wide association studies (GWAS) have found robust evidence for a latent genomic factor for externalizing disorders 11,12 , composed of input GWAS related to substance use disorders, risky sexual behaviors, personality characteristics, and neurodevelopmental disorders. Importantly, genetic liability for externalizing disorders overlaps with other phenotypes of public health relevance, such as suicidal thoughts and behaviors 11,[13][14][15] , SUDs 11,[16][17][18] , and a range of other medical conditions (e.g., ischemic heart disease, liver disease, viral hepatitis) 11 . The widespread impact of risk for externalizing disorders makes it a potential target for early intervention and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Non-suicidal self-injury and suicidal thoughts and behaviors are transdiagnostic, co-occurring with psychiatric disorders ranging from bipolar disorder [20] to eating disorders [21], but are most frequently studied in the context of depression. Polygenic risk scores (PRS; an estimate of one's genetic liability to a trait of interest) for major depressive disorder, depressive symptoms and/or broad depression are associated with self-reported suicidal thoughts and behaviors ranging from selfharm (in general) to suicidal ideation, suicide attempt and death by suicide [19,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…46) [17] and suicide attempt (r g =0.78) [18] and depression [29] is also not perfectly genetically correlated with death by suicide (r g =0.42) [30]. Some studies have found significant associations between observed suicidal thoughts and behaviors and PRS of selfharm [16,23] and suicide attempt [18,24,31]. However, with the exception of a recent study from Mullins et al [18] which identified a significant association between suicide attempt and a PRS constructed from a GWAS of suicide attempt conditioned on major depressive disorder [18], little research has explored whether genetic liability to non-suicidal self-injury and suicidal thoughts and behaviors that are independent from genetic liability to depression explain variance in suicidal thoughts and behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation